The Prognostic Role of GLIM Criteria in Postoperative Outcomes after Upper Gastrointestinal Cancer Surgery: A Meta-Analysis of Observational Studies. (7th February 2023) - Lidoriki, Irene; Frountzas, Maximos; Mela, Evgenia; Papaconstantinou, Dimitrios; Vailas, Michail; Sotiropoulou, Maria; Koliakos, Nikolaos; Toutouzas, Konstantinos G.; Schizas, Dimitrios
Abstract: Oncologic patients often suffer from malnutrition, which might negatively affect treatment outcomes. Global Leadership Initiative on Malnutrition (GLIM)-based malnutrition is associated with short- and long-term outcomes in cancer patients. The aim of the current meta-analysis was to determine the impact of GLIM-defined malnutrition on postoperative complications and survival in esophageal and gastric cancer patients. A systematic search was conducted to identify studies published until February 2022 that assessed the association between GLIM criteria and short- and long-term outcomes in esophageal and gastric cancer patients. We included seven observational studies reporting on a total of 3662 patients with esophageal and gastric cancer. GLIM-defined malnutrition was associated with increased overall complications (pooled HR 2.58, 95% CI 1.45–4.59, p = 0.001). Malnutrition was significantly associated with decreased overall survival (pooled HR 1.63, 95% CI 1.18–1.84, p = 0.003) as well as with decreased disease-free survival (pooled HR 1.78, 95% CI 1.36–2.33, p < 0.0001). GLIM-based malnutrition was associated with an increased risk for developing postoperative complications and impaired survival of esophageal and gastric cancer patients. Our findings support the use of GLIM criteria in clinical practice as a relatively simple and reliable tool for assessing the nutritional status of oncologic patients.